1993
DOI: 10.1152/ajprenal.1993.264.6.f1060
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate-activated adenylyl cyclase in fluid-transporting tissues

Abstract: A bicarbonate-stimulated adenylyl cyclase (AC) activity was found in ocular ciliary processes, which secrete the aqueous humor of the eye. Other fluid-transporting tissues also showed HCO3(-)-stimulated AC activity. Relative to basal, the response to 10 mM NaHCO3 was greatest in the particulate fraction of bovine ciliary processes, followed by bovine corneal endothelium, bovine choroid plexus, and rat kidney (medulla and cortex). However, no activity was detectable in bovine retina, cerebral cortex, or cerebel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 0 publications
7
41
0
Order By: Relevance
“…Total RNA was isolated from testes from wild-type, heterozygous, and homozygous littermates by using TRIzol (GIBCO͞BRL). First-strand synthesis was performed by using oligo(dT) 15 (Promega) and pd(N) , (Amersham Biosciences) primers and SuperScript II RNase H reverse transcriptase (Invitrogen) according to the manufacturer's instructions. Reverse-transcribed products were then PCR amplified for 17, 20, 23, and 26 cycles with the following primers: mSAC RNA-509F, 5Ј-GGCGGTGGATGATGTCCGCC-3Ј; and mSAC RNA-1053R, 5Ј-GGGAAGCCGAAGACACA-GAGG-3Ј.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was isolated from testes from wild-type, heterozygous, and homozygous littermates by using TRIzol (GIBCO͞BRL). First-strand synthesis was performed by using oligo(dT) 15 (Promega) and pd(N) , (Amersham Biosciences) primers and SuperScript II RNase H reverse transcriptase (Invitrogen) according to the manufacturer's instructions. Reverse-transcribed products were then PCR amplified for 17, 20, 23, and 26 cycles with the following primers: mSAC RNA-509F, 5Ј-GGCGGTGGATGATGTCCGCC-3Ј; and mSAC RNA-1053R, 5Ј-GGGAAGCCGAAGACACA-GAGG-3Ј.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, an essential and distinct function in the sAC-mediated cAMP signaling during late spermatogenesis has been hypothesized (5). In addition to testes, sAC protein has also been detected in choroid plexus and kidneys (5), which are tissues known to be able to modulate bicarbonate concentration and show AC activity (15). Intriguingly, in testes, sAC mRNA appears to be localized in cell types typical of late stages of spermatogenesis, i.e., from round spermatids to early elongated spermatids (16).…”
mentioning
confidence: 99%
“…31,32 These findings are consistent with the HCO 3 2 -stimulated adenylyl cyclase activity previously described in rat kidney. 33 cAMP directly stimulates V-ATPase membrane accumulation and proton secretion by A-type intercalated cells in the kidney (Figure 1), 23 and the stimulatory effect of HCO 3 2 on V-ATPase translocation in tissue slices in vitro is inhibited by incubation with the sAC inhibitor, H7. 22 That sAC-mediated cAMP signaling may constitute a general sensing mechanism for regulating V-ATPase-mediated proton transport is supported by observations from other proton transporting tissues including the epididymis 31 and the teleost intestine 34 and teleost gill.…”
Section: Soluble Adenylyl Cyclasementioning
confidence: 99%
“…Following up on the work of Mittag et al, 19 we performed cAMP forming assays and found that the CB of both human and pig contains a high level of bicarbonate-sensitive AC activity. The sensitivity of this activity to the sAC-specific inhibitor KH7 strongly suggested that the enzyme responsible is sAC.…”
Section: Sac Expression In the Cb And Tmmentioning
confidence: 98%
“…To understand how this pathway might work, we considered that Best2 functions as a bicarbonate channel. In 1993, Mittag et al 19 reported a bicarbonate-sensitive adenylyl cyclase (AC) activity in the rabbit CB. Reasoning that a bicarbonate-sensitive enzyme in the NPE could function downstream of Best2, we focused on this bicarbonate-sensitive AC activity.…”
Section: Bestrophinsmentioning
confidence: 99%